Group Counseling With Choice Theory To Increase Student Achievement Motivation - Eko Hardi Ansyah (Universitas Muhammadiyah Sidoarjo, 2013)
The Student Achievement Motivation is an encouragement of student to obtain the learning achievement. The low of this motivation can affect the low of learning achievement. In consequence, it required an effort to improve this achievement motivation. The Group Counseling represent counseling that utilizing group to teach the client about how to think, plan, and behave effectively which is hypothesized could improve the student achievement motivation. This research aims to know the effectiveness of group counseling with choice thery to improve the student achievement motivation. This research is conducted by experimental design to 18 students with low learning achievement. The subjects were divided into two groups, that is, control and experimental group. In control group, researcher doesn't give the treatment. In experimental group, the researcher give the treatment in the form of group counseling with choice theory. Data analyzed for the result of student achievement tha conducted in pretest and posttest with covarian analysis. The result shows that there is different between control and experimental group with F(2,15) = 5,545; p = 0,033; p < 0,05; n2 = 0,27, so hypothesis that there is different between the student achievement motivation with low learning achievement based on participation in group counseling with choice theory is accepted. Thereby, the group counseling with choice theory treatment is proven to improve the student achievement with low learning motivation in experimental group. This treatment contribution to improve the student achievement motivation with low learning achievement is about 27%. So that this treatment could be conducted to solve the low learning achievement student.